RANDAI AS REVITALIZATION OF LOCAL WISDOM VALUES OF MINANGKABAU (Anthropolinguistic Case Study) - Aprilyanti Aprilyanti (Universitas Potensi Utama, 2019)
Randai is indigeneous oral literature that performed and seen as an interaction medium that has been rooted in Minangkabau society from generation to generation. The purpose of the study was to describe the local wisdom values of Minangkabau in performance of randai. The instrument used for collecting data was written test. The method of the study used library research by Miles Huberman (2014). These data were analysed applying qualitative descriptive method to find out and describe the local wisdom values of Minangkabau in performance of Randai based on antropolinguistics study. The results of the study showed that there can be found the local wisdom values of minangkabau culture from performance of randai. Hence, it was concluded that randai should be revitalised and inventorised not for the Minangkabau society but also for Indonesian culture.